Information System Program Design Of Panti Asuhan - Nurul Afni; Agus Salim; Yana Iqbal Maulana; Ade Nugraha; Rachman Komarudin (Journal of Information System, Informatics and Computing, 2022)
The development of information systems at this time encourages every element to be more advanced, productive and make the best use of technology in order to get convenience, accuracy, efficiency, flexibility in every human activity. In order to keep pace with the development of this era, we need a system that can support all needs and all activities. A social institution that works to protect orphans and orphans which in practice has not yet been computerized. All administrative processes for foster children, guardians or recording donations and all forms of documentation are still done manually, so it is possible that an error occurred during the creation of foster child data, donation data or financial reports. Therefore, the researchers created an information system that can replace the manual system that is currently running. The result of this research is a web-based application using the Waterfall SDLC (Software Development Life Cycle) software development method. With this system, it is hoped that it can provide assistance to the orphanage management in processing all administrative data and donations.